New COVID-19 saliva-based test: How good is it compared with the current nasopharyngeal or throat swab test? - Kai-Feng Hung; Yi-Chen Sun; Binghong Chen; Jeng‐Fan Lo; Chao‐Min Cheng; Cho-Yi Chen; Cheng‐Hsien Wu; Shou‐Yen Kao (2020)
As of April 15, 2020, the US Food and Drug Administration has granted emergency use authorization to a first saliva test for diagnosis of severe acute respiratory syndrome coronavirus 2 infection, the device developed by RUCDR Infinite Biologics laboratory, Rutgers University. A key feature that distinguishes the saliva-based test from nasopharyngeal or oropharyngeal (throat) swabs is that this kit allows self-collection and can spare healthcare professionals to be at risk during collecting nasopharyngeal or oropharyngeal samples, thereby preserving personal protective equipment for use in patient care rather than sampling and testing. Consequently, broader testing than the current methods of nasal or throat swabs will significantly increase the number of people screening, leading to more effective control of the spread of COVID-19. Nonetheless, a comparison of saliva-based assay with current swab test is needed to understand what and how we can benefit from this newly developed assay. Therefore, in this mini-review article, we aimed to summarize the current and emerging tools, focusing on diagnostic power of different clinical sampling and specimens.